Analisis Profesionalisme Guru Memperhatikan Faktor Pendidikan, Kompetensi dan Pengalaman Mengajar (Studi pada Guru YPI Ummul Ayman Samalanga Kabupaten Bireuen) - Turrahmi, Sarah; Kamaruddin, Kamaruddin (Singkite Journal, 2024)
The research analyzes the level of teacher professionalism related to teacher education, competency and teaching experience. The study was conducted on 62 teachers at the Ummul Ayman Samalanga Islamic Education Foundation, Bireuen Regency. Applying associative quantitative methods with an inferential statistical approach through path analysis models. The research results showed that (1) teacher professionalism was supported directly and indirectly by their education, with an influence of 52.63%, while competency and teaching experience factors also contributed positively, each amounting to 49.14%. and 57.24%. (2) Simultaneously the level of education, competency and teaching experience influences teacher professionalism by 62.5%.